Treatment Techniques to Reduce Cardiac Irradiation for Breast Cancer Patients Treated with Breast-Conserving Surgery and Radiation Therapy: A Review - Beck, Robert E.; Kim, Leonard; Yue, Ning J.; Haffty, Bruce G.; Khan, Atif J.; Goyal, Sharad (Frontiers in Oncology, 2014)
Thousands of women diagnosed with breast cancer each year receive breast conserving surgery followed by adjuvant radiation therapy. For women with left-sided breast cancer, there is risk of potential cardiotoxicity from the radiation therapy. As data has become available to quantify the risk of cardiotoxicity from radiation, strategies have also developed to reduce the dose of radiation to the heart without compromising radiation dose to the breast. Several broad categories of techniques to reduce cardiac radiation doses include breath hold techniques, prone positioning, Intensity Modulated Radiation Therapy, and Accelerated Partial Breast Irradiation, as well as many small techniques to improve traditional 3 dimensional conformal radiation therapy. This review summarizes the published scientific literature on the various techniques to decrease cardiac irradiation in women treated to the left breast for breast cancer after breast conserving surgery.